The Emotional Power of Space - Bêka, Ila; Lemoine, Louise (S.l. : B&P, Bêka & Partners Publishers, 2023)
Bilbao, Tatiana ; Fujimori, Terunobu ; Herzog, Jacques ; Holtrop, Anne ; Ishigami, Junya ; Jain, Bijoy ; Nishizawa, Ryue ; Pallasmaa, Juhani ; Premthada, Boonserm ; Radić, Smiljan ; Sejima, Kazuyo ; Siza, Álvaro
boek